Association of Risk of Obstructive Sleep Apnea With Thyroid Eye Disease: Compressive Optic Neuropathy. Issue 3 (May 2019) - Habib, Larissa A.; Godfrey, Kyle J.; Mathews, Priya; De Rojas, Joaquin; Kazim, Michael
Abstract : Purpose: To evaluate the association of risk of obstructive sleep apnea (OSA) and thyroid eye disease-compressive optic neuropathy (TED-CON). Methods: The authors performed a retrospective observational study. All TED patients evaluated by the principal investigator over the past 5 years were screened with the snoring tired observed pressure (STOP)-Bang questionnaire to assess their risk for OSA. Patients were grouped into 2 age-matched cohorts based on the presence (TED-CON) or absence of CON. The groups were then compared using chi-square analysis for binary variables and Student t test for continuous variables. Results: Three hundred twenty-six patients were identified to have TED. Of those, 109 were enrolled in the study. The prevalence of high risk of OSA was significantly higher in the TED-CON (59.2%) when compared with the noncompressive TED group (32.8%; p = 0.006). Conclusions: Obstructive sleep apnea and TED have each been independently associated with elevated serologic and tissue inflammatory mediators. The systemic inflammation associated with OSA has been implicated in the pathogenesis of disease states aggravated by untreated OSA. Effective treatment of OSA decreases the levels of circulating inflammatory mediators. Currently, smoking is the only known modifiable risk factor in TED. There is evidence to implicate the pathologic elevation of inflammatory cytokines in the mechanism of smoking on TED. This preliminary investigation reveals a significantly greater prevalence of OSA risk factors among patients with TED-CON, suggesting that this may be another modifiable risk factor associated with TED. Based on screening with the STOP-Bang questionnaire, there is a higher percentage of patients at high risk of OSA with TED with CON than with TED without CON. Abstract : This observational study identifies an association between risk of obstructive sleep apnea and thyroid eye disease-compressive optic neuropathy, representing a potential modifiable risk factor in patients with thyroid eye disease.